Truly Personalized Medicine? - Smith, Lauren B. (The Hastings Center report, 2014)
The patient wished to receive an experimental drug that she was instrumental in developing. After her diagnosis, she had investigated treatments that might help her condition and discovered that a specific compound could be beneficial. To further the development of this potential drug, she obtained preclinical data, founded a company, and sought investment from venture capitalists. The company was about to begin phase I testing, but the clinical trial had not yet opened. In addition, she would not have been a candidate for the study, as it excluded patients with advanced disease. To be able to administer this drug to her, the patient's team of oncologists was in the process of drafting an individual patient investigational new drug application, including the protocol for the drug's delivery, to the Food and Drug Administration. The company developing the drug had preliminarily agreed to provide it. This protocol was also under review by the institutional review board of the university, and the ethics committee was consulted to determine whether she should receive the drug.